Clinical evaluation of motor neuron disease in Erbil Governorate: A cross-sectional study - Mansour Fakher Hado; Abdulrahman Aziz Rasoul (Advanced Medical Journal)
Background & Objectives: Melasma is an acquired hyperpigmented patches dispersed symmetrically on body parts that are exposed to sun, mostly on face of female patients. The precise etiology is obscure, but it has numerous hazards such as; ultra violet exposure, genetic factors, hormonal imbalances like thyroid hormone abnormalities. In this study we aimed to evaluate serum thyroid hormones levels in melasma patients.